AN EXAMINATION OF CUSTOMERS’ PERCEIVED RISK AND TRUST AS ANTECEDENTS FOR ONLINE PURCHASING OF MEDICAMENTS - Ariffin, IA; Yajid, Mohd Shukri Ab; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
A number of studies have been carried out to understand the impact of the perceived risk and trust, as well as their influential antecedents on the customers’ intention to buy medicaments online. However, the majority of these researches have concentrated on common factors, such as financial risks, delivery risks, and information security, all of which similarly affect all the products offered in online stores, while the parameters that specifically influence online purchasing of medicaments have not been examined. This study aims to enumerate this gap in existing research and attempts to offer a picture of specific determinants that significantly influence the customers’ perceived risk and trust during online shopping of medicaments. In order to collect the data needed for the examination of this model, an online questionnaire was distributed, which resulted in 157 valid responses. The outcomes of the present thesis could also provide customers a better understanding of the challenges associated with online buying of medicaments and encourage them to make more responsible decisions in order to avoid further complications.